International Terrorism and Citizenship: Quo-Vadis Citizenship Status (ex) ISIS Members - Syam, Roqiyul Ma’arif; Fitriya, Nauval; Elkoshly, Salim; Afiah, Khoniq Nur (Graduate School of Syarif Hidayatullah State Islamic University Jakarta, 2022)
The phenomenon of the emergence of the international terrorist group ISIS has succeeded in recruiting members from various countries in the world. This serious threat to national security is closely related to the issue of a person's citizenship status, either as a member or as a mere sympathizer. Several countries responded to the entry of their nationals into this international terrorist group with proposals to revoke their citizenship. On the one hand, international terrorism is a serious threat to state sovereignty, on the other hand the problem of denationalizing a former member or affiliated with ISIS is not an easy thing. Citizenship status is a human right that is protected, both in legal instruments in Indonesia and in international legal instruments. Citizenship law in Indonesia regulates in such a way regarding loss of citizenship. From an international perspective, international legal instruments strictly prevent member states from carrying out such denationalization efforts.